2015
DOI: 10.1007/s12185-015-1841-x
|View full text |Cite
|
Sign up to set email alerts
|

CD20-positive primary gastric T-cell lymphoma poorly responding to initial treatment with rituximab plus CHOP, and a literature review

Abstract: There have been rare reported cases of peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) that co-expressed CD20. A 44-year-old Japanese male was initially misdiagnosed as CD20-positive diffuse large B-cell lymphoma with a background of reactive CD3-positive T-cells in the stomach. After four cycles of R-CHOP [rituximab plus cyclophosphamide (CY), doxorubicin, vincristine, and prednisolone (PSL)], total gastrectomy with regional lymph node dissection was performed due to the poor response to R-CHOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Immunohistochemistry of the small intestine demonstrated that most of the lymphocytes were positive for CD20, CD3 and granzyme B. The CD20-positive primary gastric T-cell lymphoma has been previously reported in humans [8]. The CD20 antigen, a transmembrane protein that functions as a calcium channel, has long been designated a pan-B antigen that is present on a wide range of normal and neoplastic B lymphocytes.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Immunohistochemistry of the small intestine demonstrated that most of the lymphocytes were positive for CD20, CD3 and granzyme B. The CD20-positive primary gastric T-cell lymphoma has been previously reported in humans [8]. The CD20 antigen, a transmembrane protein that functions as a calcium channel, has long been designated a pan-B antigen that is present on a wide range of normal and neoplastic B lymphocytes.…”
mentioning
confidence: 94%
“…The CD20 antigen, a transmembrane protein that functions as a calcium channel, has long been designated a pan-B antigen that is present on a wide range of normal and neoplastic B lymphocytes. However, CD20 has been identified in a small subset of normal and neoplastic T lymphocytes using flow cytometry [8]. Although the diagnosis is not well-defined for dogs, we regarded this GI lymphoma as T-cell lymphoma based on the result of positive granzyme B staining, which was expressed exclusively by cytotoxic T lymphocytes.…”
mentioning
confidence: 99%
“…Kakinoki et al proposed that the efficacy of rituximab for CD20-positive TCL may be associated with intensity of CD20 expression in tumor T-cells and its homogeneity in the tumor tissue. 31 Unfortunately, none of the six cases were treated with rituximab. Further clinical studies are required to determine whether the addition of rituximab offers any survival advantage to these patients with CD20positive ENKTCL.…”
Section: Pathological Findings and Resultsmentioning
confidence: 99%
“…However, the efficacy for CD20‐positive T/NK‐cell lymphomas is yet to be known. Kakinoki et al proposed that the efficacy of rituximab for CD20‐positive TCL may be associated with intensity of CD20 expression in tumor T‐cells and its homogeneity in the tumor tissue . Unfortunately, none of the six cases were treated with rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Kakinoki et al [ 11 ] reported the successful treatment of 11 patients with CD20-positive T-cell lymphoma with rituximab alone or with rituximab plus chemotherapy. Of these patients, 3 showed strong CD20 staining and 2 showed weak CD20 staining; all were treated with RCHOP.…”
Section: Discussionmentioning
confidence: 99%